Marketing strategy of Oracle Ireland in the B2B environment. - Lim, Chern Chern. (2008)
Our case study serves to assist Oracle Ireland in their new direction by analyzing marketing trends of this segment that emerges in the historical sales data for two fiscal years. We have complemented the data analysis with qualitative studies conducted on interviews with Oracle’s key personnel and research conducted via the Internet.